(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
This paper presents a numerical study of the non-cavitating and cavitating flow around CAV 2003 hydrofoil. The phenomenon of cavitation is modeled through a mixture model. For the numerical solution of cavitating flow a bubble dynamics cavitation model is used to describe the generation and evaporation of vapor phase. The non-cavitating study focuses on the influence of the turbulence model and different mesh sizes used in the computation. Three turbulence models such as Spalart-Allmaras, Shear Stress Turbulence (SST) k-? model, RNG k-? with enhanced wall treatment are used to capture turbulent boundary layer along the hydrofoil surface. The results predicted by these models are compared with each other. The cavitating study first presented an unsteady behavior of the partial cavity attached to the foil. Then, an analysis of a supercavitating condition is performed. The predicted results show good agreement with results published by other researchers. DOI: 10.3329/jname.v7i2.5270